Effect of Footwear on Dynamic Stability during Single-leg Jump Landings - Bowser, Bradley J; Rose, William C.; McGrath, Robert; Salerno, Jilian; Wallace, Joshua; Davis, Irene S. (International Journal of Sports Medicine, 2017)
Barefoot and minimal footwear running has led to greater interest in the biomechanical effects of different types of footwear. The effect of running footwear on dynamic stability is not well understood. The purpose of this study was to compare dynamic stability and impact loading across 3 footwear conditions; barefoot, minimal footwear and standard running shoes. 25 injury free runners (21 male, 4 female) completed 5 single-leg jump landings in each footwear condition. Dynamic stability was assessed using the dynamic postural stability index and its directional components (mediolateral, anteroposterior, vertical). Peak vertical ground reaction force and vertical loadrates were also compared across footwear conditions. Dynamic stability was dependent on footwear type for all stability indices (ANOVA, p<0.05). Post-hoc tests showed dynamic stability was greater when barefoot than in running shoes for each stability index (p<0.02) and greater than minimal footwear for the anteroposterior stability index (p<0.01). Peak vertical force and average loadrates were both dependent on footwear (p≤0.05). Dynamic stability, peak vertical force, and average loadrates during single-leg jump landings appear to be affected by footwear type. The results suggest greater dynamic stability and lower impact loading when landing barefoot or in minimal footwear.
Keywords: minimal footwear; barefoot running; proprioception; balance